CommUNIty-Led development: A partnership to realize Aboriginal Elders' vision for change. Issue 5 (20th October 2021) - McCausland, Ruth; Spencer, Wendy; MacGillivray, Peta; Robinson, Virginia; Hickey, Vanessa; Baldry, Eileen; McEntyre, Elizabeth
ABSTRACT: This article outlines the development of "Yuwaya Ngarra-li" (YN), a holistic, community-led partnership with a university that aims to realize Aboriginal Elders' vision for wellbeing in their community. The Dharriwaa Elders Group (DEG), a community-controlled organization in Walgett, a remote town in New South Wales (NSW), Australia, invited the University of New South Wales (UNSW) to partner with them to progress their long-held vision for systemic change. This partnership aims to improve the environment, life pathways, and wellbeing of Aboriginal people living in Walgett through collaboration on evidence-based initiatives, research and building local community capabilities and control. YN builds on decades of strong advocacy, community development, and participatory research that has focused on addressing structural injustices and inequity through centering Indigenous knowledges, worldviews, and rights. This innovative partnership is contributing to the evidence base for community-led solutions, with implications for research, policy and practice.